Relationship between continuous assessment and academic performance of secondary school students in english language and mathematics in Ibadan (2012)
This study examined the effect of continuous assessment on academic performance of students in English language and Mathematics in secondary schools. The study adopted a descriptive survey research that utilized an ex-post facto design to collect secondary data of 840 students used for this study. Four hypotheses were tested for and analysed using Pearson's Product Moment Correlation and t-test for independent samples analysis tested at the O.05 level of significance. The result of the analysis showed that there were positive significant relationship between continuous assessment and academic performance in English language and Mathematics. Government, school administration and teachers should ensure effective implementation and practice of continuous assessment to improve on students' performance. Parents and the students should also respond positively to the feedback given by continuous assessment to enhance its remediation as well as teacher dwelling on its outcome to adjust the teaching and learning process. The government should also improve on the conditions of teaching and learning in the public secondary schools.